Snowpit Chemistry - Methods Comparison, WAIS Divide, Antarctica - Kreutz, Karl; Koffman, Bess (IEDA: US Antarctic Program Data Center, 2015)
Abstract: Measurements of a suite of trace elements in snow pit samples from WAIS Divide, Antarctica.